Peer review of teaching: using the nominal group technique to improve a program in a university setting with no previous experience - Barrios-Rodríguez, Rocío; Salcedo-Bellido, Inmaculada; Jiménez-Moleón, José Juan; Lozano-Lorca, Macarena; Galiano-Castillo, Noelia; Cobos, Enrique José; Vílchez-Rienda, José Dámaso; Olmedo-Requena, Rocío; Amezcua-Prieto, Carmen; Martín-Peláez, Sandra; González-Doménech, Carmen María; Arrebola Moreno, Juan Pedro; et al. (International Consortium for Educational Development, 2022)
Peer Review of Teaching (PRT) programmes provide benefits for both the observer and the observed colleague, but there are no PRT programmes implemented in Spanish Universities. A PRT pilot programme involving 14 volunteer teachers from University of Granada (Spain) was carried out. Each participant observed a colleague while giving a lesson, afterwards filling out a checklist to provide appropriate feedback. To evaluate its effectiveness to detect aspects of teaching that could be improved, pre- and post-observation anonymous questionnaires were self-administered. The programme was more effective detecting teacher weaknesses than strengths. All participants who thought they would feel nervous/ashamed declared to feel better than expected after the observation. The programme met the expectations of all participants. Proposals for the improvement of the programme were agreed through a nominal group technique, where two questions were formulated: How could the PRT programme be improved? and How could university teachers be encouraged to participate in a PRT programme? The proposal with the highest score to improve the PRT programme was To ensure that the observer and the observed do not belong to the same area of knowledge, and the proposal with the highest score to encourage participation in PRT programmes was To provide information before participating in the programme to alleviate possible fears or worries. In summary, our PRT pilot programme allowed self-reflection on teaching, identifying weaknesses while minimizing preconceived negative feelings, and providing valuable information for further larger studies with the potential to improve the quality of teaching in the Spanish context.
Keywords: Enseñanza superior; Educación - Evaluación; Peer review of teaching; Higher education; Nominal group technique